STRATEGI MENINGKATKAN DAYA SAING HOTEL SULTHAN BANDA ACEH MELALUI PENDEKATANANALISIS SWOTSTRATEGI MENINGKATKAN DAYA SAING HOTEL SULTHAN BANDA ACEH MELALUI PENDEKATANANALISIS SWOT - Rizky Syahputra; A. Rahim Matondang; Suwito Suwito (Jurnal Riset Akuntansi dan Bisnis)
Room occupancy rate Sulthan Hotel room occupancy rate is lower than the overall hotel room in Banda Aceh. One of the factors that lead to failure to achieve the occupancy rate at the Hotel Sulthan hotel is a low competitiveness compared to competitor hotels. The aim of this study was to identify factors internal and external factors affecting the low level of room occupation and to develop effective strategies to improve the competitiveness of Sulthan Hotel Banda Aceh. This type of research in the study is action research, with data analysis SWOT and QSPM. Market Penetration Strategy is a strategy that was formulated so that Sulthan Hotel Banda Aceh can improve the competitiveness of the hotel. Market penetration strategy through a series of more aggressive marketing activities in the form of hotel promotion and a series of co-operation with companies and government agencies.